2023
DOI: 10.1080/19490976.2023.2183685
|View full text |Cite
|
Sign up to set email alerts
|

Circulating androgen regulation by androgen-catabolizing gut bacteria in male mouse gut

Abstract: Abnormally high circulating androgen levels have been considered a causative factor for benign prostatic hypertrophy and prostate cancer in men. Recent animal studies on gut microbiome suggested that gut bacteria are involved in sex steroid metabolism; however, the underlying mechanisms and bacterial taxa remain elusive. Denitrifying betaproteobacteria Thauera spp. are metabolically versatile and often distributed in the animal gut. Thauera sp. strain GDN1 is an un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…GM is involved into the process of deglucuronidation, thus being capable of increasing free androgen levels in the intestine. 59 Interestingly, some specific intestinal bacteria utilize sexual hormones, such as Steroidobacter Denitrificans, and Comamonas Testosteroni. 60 In fact, sex steroids serve as a carbon source for gut bacteria; eventually, host circulating androgen levels may be regulated by androgen-catabolizing gut bacteria.…”
Section: Gm and Sex Hormones Regulationmentioning
confidence: 99%
See 4 more Smart Citations
“…GM is involved into the process of deglucuronidation, thus being capable of increasing free androgen levels in the intestine. 59 Interestingly, some specific intestinal bacteria utilize sexual hormones, such as Steroidobacter Denitrificans, and Comamonas Testosteroni. 60 In fact, sex steroids serve as a carbon source for gut bacteria; eventually, host circulating androgen levels may be regulated by androgen-catabolizing gut bacteria.…”
Section: Gm and Sex Hormones Regulationmentioning
confidence: 99%
“…60 In fact, sex steroids serve as a carbon source for gut bacteria; eventually, host circulating androgen levels may be regulated by androgen-catabolizing gut bacteria. 59 A group of researchers demonstrated that the levels of testosterone (T) correlated with bacterial density in the intestine. Using a specific, sensitive gas chromatography-tandem mass spectrometry method, they detected high levels of glucuronidated T and dihydrotestosterone (DHT) in small intestinal content of mice of both sexes, whereas in the distal intestine there were high levels of free DHT, exceeding serum levels by over 20-folds.…”
Section: Gm and Sex Hormones Regulationmentioning
confidence: 99%
See 3 more Smart Citations